A Study of Dramatic Action and Emotion Using a Systematic Scan of Stick Figure Configurations - Raindel, Noa; Liron, Yuvalal; Alon, Uri (Frontiers in Physics, 2021)
Comprehending the meaning of body postures is essential for social organisms such as humans. For example, it is important to understand at a glance whether two people seen at a distance are in a friendly or conflictual interaction. However, it is still unclear what fraction of the possible body configurations carry meaning, and also what is the best way is to characterize such meaning. Here we address this by using stick figures as a low dimensional, yet evocative, representation of body postures. We systematically scanned a set of 1470 upper-body postures of stick figures in a dyad with a second stick figure with a neutral pose. We asked participants to rate the stick figure in terms of both 20 emotion adjectives like sad or triumphant, and 8 active verbs that connote intent like to threaten and to comfort. Stick figure configuration space was dense with meaning: people strongly agreed on almost half of the configurations. Meaning was generally smooth in the sense that small changes in posture had small effect on meaning, but certain small changes had large effect. Configurations carried meaning in both emotions and intent, but the intent verbs covered more configurations. The effectiveness of intent verbs in describing body postures aligns with a theory, originating from theatre, called dramatic action theory. This suggests that, in addition to the well-studied role of emotional states in describing body language, much can be gained by using also dramatic action verbs which signal the effort to change the state of others. We provide a dictionary of stick figure configurations and their perceived meaning. This systematic scan of body configurations might be useful to teach people and machines to decipher body postures in human interactions.